Penyusunan Bibiliografi Beranotasi Karya Buya Hamka di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Zalino, Fitria Putri; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
This article aims to describe how the preparation of an annotated bibliography Buya Hamka work in UPT. Library of Bung Hatta Bukittinggi. The method used is descriptive method that describes the physical characteristics of library materials to: (1) observation of spaciousness to know the collection Buya Hamka in UPT. Library of Proklamator Bung Hatta Bukittinggi; (2) The record field used to record things during the study. Based on the findings in the field is known that the preparation of bibliographic work Buya Hamka are not in the Library of Proklamator Bung Hatta then in need of making an annotated bibliography. Based on the discussion can be concluded the stage of making the bibliography are: (1) Determination of bibliographic titles; (2) The collection of library materials; (3) Selection of library materials, aims to determine the theme of the bibliography; (4) grouping or classification; (5) Preparation of keywords; (6) Preparation of the index; (7) Making or typing bibliographies; (8) Examination of the final draft of the examination of article bibliographies of errors and spelling and punctuation. Keywords: Preparation, bibliography, annotated, Buya Hamka